Návrh úpravy zvoleného úseku vodního toku - Vyplel, Adam (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Bakalářská práce je zaměřena na návrh úpravy vybraného úseku toku Veverka v katastrálním území Brno-Bystrc, a to v ř. km 0,632 až 0,918. K úpravě je přistoupeno především jako návrh stabilizace poškozených břehů pomocí kamenné rovnaniny, plůtku z tyčoviny, kamenného záhozu a drátokamenné matrace. Vhodnost daných opatření byla stanovena na základě stávajícího stavu toku. Na úseku se nachází sedimentační nádrž, na jejímž vtoku se nachází balvanitý skluz, který byl podroben posouzením na stabilitu skluzové plochy Pomocí programu HEC-RAS je ověřena kapacita koryta toku na jednoletý průtok Q1. Následně došlo k návrhu vegetačního doprovodu a břehových porostů vybraného úseku toku tak, aby došlo k přirozenému napojení toku na okolní lesní porost.

The bachelor thesis focuses on the draft amendment of the selected section of the Veverka watercourse in the cadastral area of Brno-Bystrc in the km 0,632 to 0,918 of watercourse. The adaptation is mainly done as a draft for the stabilization of damaged banks by means of stone retaining wall, wooden pole fencing, stone riprap and gabions. The suitability of the given measures was determined on the basis of the current state of the watercourse. In the chosen section there is a sedimentation reservoir with a boulder chute that has been subjected to an assessment of the stability of the slope surface. Then the HEC-RAS program is used to verify the flow capacity of the whole flow channel for the one-year flow Q1 condition. Subsequently, the vegetation accompaniment and the coastal vegetation of the selected section of the watercourse were designed in order to naturally connect the watercourse to the surrounding forest vegetation.
A draft amendment selected section of of the watercourse
Keywords: úprava; stabilizace; HEC-RAS; vegetace; balvanitý skluz; amendment; stabilization; HEC-RAS; vegetation; boulder chute